Unexpected influence of prismatic plate-shaped precipitates on strengths and yield anisotropy in an extruded Mg-0.3Ca-1.0In-0.1Al-0.2Mn (at.%) alloy. (August 2019) - Nakata, T.; Bhattacharyya, J.J.; Agnew, S.R.; Kamado, S.
Abstract: The stress-strain response of an extruded Mg-0.3Ca-1.0In-0.1Al-0.2Mn (at. %) alloy containing prismatic plate-shaped precipitates was measured. An Elasto-Viscoplastic Self-Consistent polycrystal plasticity code was used to evaluate the effect of precipitation hardening on individual deformation modes. The results reveal the precipitates (whose shape is ideal according to the Orowan bowing model) are sheared by basal dislocations, limiting their strengthening effect, and the ratio of the strength of prismatic slip to that of extension twinning is increased, resulting in an increase in the tension-compression yield anisotropy. Graphical abstract: Unlabelled Image